The potential beneficial effects of education and familiarity with cesarean section procedure and the operating room environment on promotion of anxiety and pain intensity: A randomized controlled clinical trial - Jamshid Eslami; Neda Hatami; Azadeh Amiri; Marzieh Akbarzadeh (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Anxiety before and pain intensity after cesarean section is among the factors that should be taken into consideration among the candidates for cesarean section. The present study aimed to investigate the effect of familiarity with cesarean section and the operating room environment on anxiety and pain intensity among the mothers undergoing cesarean section. METHODS: This clinical trial was conducted on 80 women referred to the hospitals affiliated to Shiraz University of Medical Sciences for cesarean section in 2018. The participants were randomly divided into a control (n = 40) and an intervention group (n = 40). The intervention group took part in four educational sessions, while the control group received the hospital's routine care. The Beck Anxiety Inventory was completed by the two groups before and after the intervention. The McGill Pain Questionnaire was also filled out by the two groups in the ward after the cesarean section. After all, the data were entered into the SPSS software, version 21, and were analyzed using independent t-test and ANCOVA. RESULTS: The results showed no significant difference between the two groups regarding the mean score of anxiety prior to the intervention. After the intervention, the mean score of anxiety was 7.98 ± 3.77 in the intervention group and 19.70 ± 6.45 in the control group, and the difference was statistically significant (P < 0.0001). Indeed, the mean intensity of pain was 43.98 ± 7.63 in the intervention group and 57.75 ± 10.69 in the control group after the intervention, and the difference was statistically significant (P < 0.017). CONCLUSION: The patients' familiarity with cesarean section and the operating room environment caused a decline in the anxiety level prior to cesarean section as well as a decrease in the score of pain after the operation. Hence, midwives and nurses have to play effective roles in decreasing pregnant women's anxiety and pain through identification of strategies for empowering them and managing their worries.